Pelatihan Augmented Reality dalam Pembelajaran Kesehatan pada Poltekkes Yogyakarta - Caraka Aji Pranata; Muhammad Fairul Filza; Giles Palendya Thessa Widyananda (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
Augmented Reality is a technology that mixes aspects that exist in the reality world and also the virtual world. In practice, AR in the world of health is interesting because it can combine digital elements with the physical environment. Poltekkes Yogyakarta is a health education institution with the implementation of health worker education with Diploma, Bachelor, and Professional grades. This educational institution is engaged under the auspices of the Center for Health Worker Education, Health Human Resources Development and Empowerment Agency, Ministry of Health of the Republic of Indonesia. In providing education with an interactive nature, Poltekkes Yogyakarta has problems in providing interactive learning materials. The problem faced by they was not understanding about using of AR as a medium for delivering teaching materials. AR was not chosen without reason, this technology was chosen because students can quickly understand the shape of the object and also from the object it can produce annotations about the details of the part they want to know. Apart from this, educators also want to provide a visualization of the teaching material books they use so that when the teacher is explaining a component in the printed book it becomes more detailed.